Nicaragua : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
This paper provides the details of the IMF's projections and estimates on Nicaragua's gross domestic product by expenditure; value added in agriculture and manufacturing; central government operations; operations of the rest of the general government and public utility enterprises; summary balance of payments; trade account indicators; public sector external debt and debt service; summary accounts of the central bank and the financial system; consumer price index; resource balance and financing of investment, and so on. It also provides the statistical appendix report on real, fiscal, monetary, and external sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet